Forest landscapes of the southern western Ghats, India Biodiversity, Human Ecology and Management Strategies - Ramesh, B.R; Gurukkal, Rajan (Mondes Indiens/South Asia, 2007)
The Western Ghats forests are endowed with large species and habitat diversity, which is nowadays under threat by increasing demographic pressure and changing land use. To address these challenges, a novel and comprehensive approach is sought from the principles of landscape ecology. Morpho-pedological features are used to delineate landscape units all over the Western Ghats of Kerala, among which the Western Anamalai region is chosen to elucidate the relative influence of physical factors, bioclimate and anthropogenic pressures on the characteristics of natural vegetation and on the status of the vertebrate fauna. Highlighting patterns of resource utilization by proximal and distant stakeholders, the book goes about identifying value-based management zones, while proposing management strategies for conservation and sustainable development.